The illusion of an information society in Information Science: the term from the critical perspective of Mattelart, Bauman and Garcia Canclini - Barros Monteiro, Ciro Athayde [UNESP]; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
This study reflects on the term information society widely used in articles in the area of Information Science, trying to comprehend whether the term is used in a passive or critical way and what impacts this notion brings to the field. To this, the aim was to analyze the use of the term information society in the area at the national and international levels. This is a literature review carried out using two databases: the Library and Information Science Abstracts, which remains a reference in the international summary and indexing service for library professionals and other information specialists, and the Base de Dados de Referencia de Artigos de Periodicos em Ciencia da Informacao, which has become a reference in research in the area of Information Science in Brazil. The results showed that more than 80% of researchers, both national and international, use the term passively in their texts. Based on these data, the article draws on the ideas of Mattelart, Bauman and Garcia Canclini and concludes by reflecting on the risks of the area accepting the notion ofinformation society uncritically and points out, through the authors, that this term was created for mitigate the atrocities promoted by the expansion of economic interests on a global scale, expanding the performance of free capital that made the world of labor mobile and replaceable, in addition to imposing the valorization of cultural and scientific production in high income countries.
Keywords: Information Society; Knowledge Society; Globalization; Global Society; Information Science